Contabilidad de Costos por Procesos en la Empresa de Café “Don Víctor” del Sr. Guamán Villamagua Víctor Emilio de la parroquia Malacatos, Cantón Loja periodo del 01 de octubre al 31 de diciembre del 2023. - Abad Zumba, Mayra Lizbeth (2024)
The Curricular Integration Work called: Cost Accounting by Processes in the Coffee Company "Don Victor" of Mr. Guaman Villamagua Victor Emilio of the Parish Malacatos, Canton Loja period from October 1 to December 31, 2023, was conducted with the purpose of applying an accounting system by processes according to the business line, which allows the owner to know and identify the unit and total costs incurred throughout the production process. In order to comply with the objectives set, we began with the collection of information by means of an interview with the owner, which allowed us to know the difficulties regarding the handling of the documentation and information that is essential for the accounting development; therefore, we proceeded to the preparation of a plan and manual of accounts, which consists of accounting codes and accounts with their respective description, consecutively we prepared the Initial Inventory in which all the goods, values, rights and obligations are recorded, establishing the company's equity, then we prepared the Initial Situation Statement; The Operations Memorandum to begin the daily registration of the accounting movements, consequently, formats were prepared for the control of materials, labor and indirect manufacturing costs, for which the requisition order for raw materials and materials was made, using the Kardex cards to control the inputs and outputs, For labor, the time card was used, which specifies the time and cost of labor for the hours worked, the payment role that facilitated obtaining values received by workers on a monthly basis, auxiliary accounts receivable that served to control the obligations that customers have with the entity and the depreciation of non-current assets that was performed using the straight line method. Then the movements were recorded in the Daily Book, to determine the balances of each of the accounts, the values were transferred to the General Ledger, after which the Trial Balance, Worksheet and Financial Statements were prepared, which reflect the following information: Assets $ 205,695.26, Liabilities $ 211.68, Equity 205,483.58, Income $2766.23, Expenses $5,309.06 and a loss at the end of the fiscal year of $2,542.83. At the end of the Curricular Integration Work, the whole process of cost accounting by processes was implemented and the respective conclusions and recommendations were made, which allows the owner to know the economic and financial situation of the company and to have a clear idea of all the costs involved in production, in order to make the right decisions and avoid unnecessary expenses.